Acute mania following COVID-19 in a woman with no past psychiatric history case report - Steven Sprenger; J. Pilar Bare; Rahul Kashyap; Luigi Cardella (BMC Psychiatry, 2022)
Abstract Background The COVID-19 pandemic that began in late 2019 is caused by infection with the severe acute respiratory syndrome coronavirus-2. Since that time, many neuropsychiatric sequelae including psychosis, neurocognitive disorders, and mood disorders have been observed. The mechanism underlying these effects are currently unknown, however several mechanisms have been proposed. Case presentation A 47-year-old woman with past medical history including hypertension and premenstrual syndrome but no psychiatric history presented to the psychiatric hospital with new onset mania. She had developed symptoms of COVID-19 and was later diagnosed with COVID pneumonia. During quarantine, she reported high levels of stress, grief, and anxiety. Seventeen days into her illness, she developed altered mental status, sleeplessness, elevated mood, talkativeness, and preoccupations. Her spouse was concerned for her safety and contacted emergency medical services who brought her to the psychiatric hospital. She had not slept for five days prior to her arrival and exhibited flight of ideas, talkativeness, and grandiose ideas. She reported a family history of bipolar disorder but no past manic or depressive episodes. She was diagnosed with acute mania and stabilized using antipsychotics, a mood stabilizer, and a short course of a benzodiazepine. Many of her symptoms improved, including her elevated mood, increased activity level, and flight of ideas though she continued to have decreased need for sleep as her benzodiazepine was tapered. She and her partner were agreeable to transitioning to outpatient care after her mood stabilized. Conclusions This report emphasizes the link between COVID-19 and neuropsychiatric symptoms. Acute mania has no recognized association with COVID-19, but similar presentations have been reported. The patient’s age and time to onset of psychiatric symptoms is consistent with previous reports. Given the growing body of evidence, this association warrants further investigation. Severe acute respiratory syndrome coronavirus-2 causes systemic inflammation and has been shown to be neurotropic. In addition, patients undergoing quarantine experience anxiety related to the disease in addition to social isolation. Psychiatric practitioners should be aware of these effects and advocate for psychiatric evaluation following COVID-19 infection. Understanding the sequelae of infectious disease is crucial for responding to future pandemics.